2024
DOI: 10.3389/fmicb.2023.1290302
|View full text |Cite
|
Sign up to set email alerts
|

Application of propidium monoazide quantitative PCR to discriminate of infectious African swine fever viruses

Yang Li,
Zewei Wang,
Jie Qing
et al.

Abstract: IntroductionThe detection of African swine fever virus (ASFV) is commonly performed using quantitative real-time PCR (qPCR), a widely used virological method known for its high sensitivity and specificity. However, qPCR has a limitation in distinguishing between infectious and inactivated virus, which can lead to an overestimation of viral targets.MethodsTo provide insights into ASFV infectivity, we evaluated the suitability of PMAxx, an improved version of propidium monoazide (PMA), as a means to differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…To address these points, a sample pre-treatment with DNA intercalants such as PMA and its derivatives (i.e., PMAxx) has been proposed to distinguish between infectious and non-infectious viruses. Recent studies have demonstrated the selective detection of various viruses using PMA, including norovirus, enterovirus, African swine fever viruses, and Red Sea Bream Iridovirus [ 20 , 21 , 22 , 23 ]. Recently, Hong et al [ 18 ] conducted in vitro experiments by inactivating or not inactivating the SARS-CoV-2 with UV light and using sodium dodecyl sulfate as a mild membrane destabilizer to increase the PMA permeability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these points, a sample pre-treatment with DNA intercalants such as PMA and its derivatives (i.e., PMAxx) has been proposed to distinguish between infectious and non-infectious viruses. Recent studies have demonstrated the selective detection of various viruses using PMA, including norovirus, enterovirus, African swine fever viruses, and Red Sea Bream Iridovirus [ 20 , 21 , 22 , 23 ]. Recently, Hong et al [ 18 ] conducted in vitro experiments by inactivating or not inactivating the SARS-CoV-2 with UV light and using sodium dodecyl sulfate as a mild membrane destabilizer to increase the PMA permeability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only genomes from intact virions will be amplified and detected, while free nucleic acids or those from non-infectious viruses are not considered by a PCR. Initially, this test was primarily used to assess the integrity of bacterial pathogens [ 19 ]; however, it has since been applied to numerous viruses [ 16 , 17 , 18 , 20 , 21 , 22 , 23 ]. With the emergence of SARS-CoV-2, the question has arisen as to whether the use of PMA can aid in identifying viruses capable of infecting and producing new viral progeny from viral remnants or incomplete viruses and free viral genomes, particularly in samples that test positive by molecular assays but have low viral loads and stay positive for prolonged periods.…”
Section: Introductionmentioning
confidence: 99%